2020
DOI: 10.2478/msp-2020-0054
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of pH-sensitive hydrogels from photo-crosslinked poly(ethylene glycol) diacrylate incorporating titanium dioxide

Abstract: The purpose of the present investigation was to prepare pH-sensitive hydrogels from photo-crosslinked poly(ethylene glycol) diacrylate (PEG-DA). Rutile titanium dioxide (TiO2) was employed to modify the PEG-DA hydrogels. The rutile titanium dioxide (TiO2) nanoparticles were prepared by direct oxidation of titanium in the presence of polyethylene glycol (PEG) at high temperature. The nanoparticles were characterized by FT-IR, XRD and SEM. The influence of experimental conditions, such as pH, type and amount of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
0
9
0
1
Order By: Relevance
“…Thus, synthetic hydrogels need modification with suitable biological components to promote signals of cellular function. On the other hand, synthetic hydrogels such as PEG represent a very good candidate for the encapsulation of various bioactive factors, drugs, and chemicals to avoid complicating systemic factors derived from hydrogels for a more controlled comparison of encapsulated materials [ 34 ]. Recently, it has been reported that the combination of arginine-glycine-aspartic acid (RGD) groups or alginate-PEG hydrogel improved the spread and proliferation of fibroblasts and enhanced the osteogenic differentiation of mesenchymal stem cells (MSCs) for 3D cell culture [ 35 ].…”
Section: Applications Of Biomaterials In 3d Cell Culturementioning
confidence: 99%
“…Thus, synthetic hydrogels need modification with suitable biological components to promote signals of cellular function. On the other hand, synthetic hydrogels such as PEG represent a very good candidate for the encapsulation of various bioactive factors, drugs, and chemicals to avoid complicating systemic factors derived from hydrogels for a more controlled comparison of encapsulated materials [ 34 ]. Recently, it has been reported that the combination of arginine-glycine-aspartic acid (RGD) groups or alginate-PEG hydrogel improved the spread and proliferation of fibroblasts and enhanced the osteogenic differentiation of mesenchymal stem cells (MSCs) for 3D cell culture [ 35 ].…”
Section: Applications Of Biomaterials In 3d Cell Culturementioning
confidence: 99%
“…Here, M ∞ is the maximum amount of drug release at the maximum time interval, while K is the rate constant [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…Titanium powder was ordered from Alfa Aesar. The complete experimental procedure of TiO 2 synthesis was reported previously in detail [29]. Donepezil HCl was a kind gift by Abdi İbrahim Company.…”
Section: Methodsmentioning
confidence: 99%
“…In the current study, we investigated the synthesis and utility of PEG-DA and PEG-DA/HEMA hydrogels filled with low concentrations of nanoparticle TiO 2 for the controlled Donepezil HCl. Previous work has shown that addiction of metals, metal oxide nanoparticles such as titanium dioxide into hydrogels develops the antimicrobial properties of hydrogels and mechanical characteristics [28][29]. The swelling degree and release capacities of the hydrogel systems and the influence of the pH medium and type of photoinitator on the release properties were also examined.…”
Section: Introductionmentioning
confidence: 99%